90 CASE REPORT: LENÈGRE'S SYNDRONE PRESENTING AS NEW ONSET ATRIAL FLUTTER. (1st January 2005) - Greene, O.; Williams, D.; Diggs, J.
Abstract : A 24 year old woman presented with symptoms of near syncope, dizziness and palpitations and was found to have typical atrial flutter. She underwent an uncomplicated right atrial flutter ablation. Three years later she presented with recurrent symptoms of dizziness and near syncope. Holter monitor showed pauses > 3 seconds and sinus arrest. An EP study showed prolonged sinus node recovery time, AV nodal disease and prolonged HV interval. This case highlights sinus nodal dysfunction manifesting as atrial flutter as the initial presentation in a patient with extensive conduction system disease most likely secondary to Lenígre's disease.